(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Fish ball was formulated with fish mince powder supplemented with potato flour along with other ingredients. Higher percentage of fish mince powder contained higher amount of protein, fat and ash but lower amount of total carbohydrate and moisture compared to that containing lower percentage of fish mince powder. The water absorption and frying time increased with the increasing percentage of fish mince powder. Fish balls prepared from the ingredients having 35% fish mince powder had the highest score in flavor rating and fish ball containing 30% fish mince powder had the highest overall acceptability. The scores on color and texture of fish balls prepared from all samples were almost same, but the scores on flavor and over all acceptability varied due to the fishy flavor because some of the panelist disliked the fishy flavor. While studying the storage period, there were no remarkable changes in case of color, flavor and texture of the prepared fish ball. No molds growth was noticed on the storage period of 90 days. So, the percentage of fish mince powder had no influence on the stability of the fish ball at room temperature. J. Bangladesh Agril. Univ. 15(1): 95-102, January 2017